Вивчення фауни безхребетних Шацького поозер’я (ХІХ століття) - Іванців, В. В.; Іванців, О. Я.; Ivantciv, V. V.; Ivantciv, O. Ya. (Волин. нац. ун-т ім. Лесі Українки, 2012)
Розглянуто історію вивчення основних груп безхребетних Шацького поозер’я в ХІХ ст. Головну увагу зосереджено на дослідженнях місцевих науковців і вчених Києва та Львова. The question of development history of the invertebrata spine groups on the terrstory of Shatsk lakes in XIX century is considered in the article. The main attention in focused on the scientific investigations, held by the local scientists and scholars of Kyyiv and Lviv.
The Study of Fauna of Invertebrata Grouhs on the Territory of Shatsk Lakes (of XIX Century)
Роботу виконано на кафедрі екології ЛНТУ
Keywords: фауна безхребетних; зоологія; озеро Світязь; fauna of invertebrata; zoology; Volhyn; Shatsk lakes